2022
DOI: 10.3390/polym14132746
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Raster Pattern on Residual Stress and Part Distortion in FDM of Semi-Crystalline Polymers: A Simulation Study

Abstract: In fused deposition modelling (FDM) based on the selected raster pattern, the developed internal thermal residual stresses can vary considerably affecting the mechanical properties and leading to distinct part distortions. This phenomenon is more pronounced in semi-crystalline than amorphous polymers due to crystallisation. Hence, this study focuses on the simulation of the FDM process of a semi-crystalline polymer (polypropylene) with raster patterns such as line (90°/90°), line (0°/90°), zigzag (45°/45°), zi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 36 publications
0
9
0
1
Order By: Relevance
“…Specimens were characterized by a slight curvature of the face in contact with the build plate, showing the effects of shrinkage and warping as observed in past works (Tekinalp et al. , 2014; Samy et al. , 2022; Wang et al.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Specimens were characterized by a slight curvature of the face in contact with the build plate, showing the effects of shrinkage and warping as observed in past works (Tekinalp et al. , 2014; Samy et al. , 2022; Wang et al.…”
Section: Methodsmentioning
confidence: 99%
“…The lateral interface between rasters is also a critical aspect of the material’s integrity; in fact, the newly fused material is deposited in a later stage with respect to the previously deposited one, with a time delay that depends on the printing speed and strategy (Sun, 2008; Sood et al. , 2012; Samy et al. , 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Cooling rates in the edge regions are significantly faster than in the central areas, owing to the better exposure of the former to the colder outer environment. This temperature profile could have implications for the mechanical properties and dimensional accuracy of FDM fabricated parts [31]. The temperature data presented in Figure 18 demonstrates the comparison of the temperature history curves, taken in pre-defined measuring point in the first deposited layer in specimens manufactured with same layer thickness of 0.15 millimetres, but varying nozzle temperature (220, 210 and 200 °C).…”
Section: Temperaturementioning
confidence: 99%
“…Samy et al [14] investigated the influence of raster patterns on residual stress and distortion using semi crystalline polymers such as polypropylene (PP). They found that the kind of raster pattern and its deposition direction influence the distortion, as thermal effects such as phase transition (amorphous to crystalline) result in density gradients, leading to stresses in multilayers.…”
Section: State Of the Art: Distortion Of Thermoplastic Componentsmentioning
confidence: 99%